Agriculture and Environment in the Eastern Nepal Himalayas - Rijal, Shiba Prasad (The Third Pole: Journal of Geography Education, 2014)
Chapagain, Prem Sagar. 2009. Agriculture and Environment in the Eastern Nepal Himalayas, VDM Verlag Dr. Muller, Germany, pp 166 + viii, acknowledgements, tables, figures, pictures, diagrams, reference and annex, paperback, price not quoted. DOI: http://dx.doi.org/10.3126/ttp.v8i0.11519 The Third Pole: Journal of Geography Vol.8-10, pp. 73-74: 2010